Human development in India: Challenges for a society in transition - Desai, Sonalde; Dubey, Amaresh; Joshi, Brij Lal; Sen, Mitali; Shariff, Abusaleh; Vanneman, Reeve (Oxford University Press, 2010)
India's rapid economic expansion has raised global interest in its complex society and the continued growth that has touched the ordinary citizen. This report highlights how poverty and affluence intersect with age-old divisions of regional inequalities, gender, caste, and religion that have long structured human development in India. Together, these economic and social forces shape every facet of Indians' lives---children's education, health and medical care, social relationships, the care of older generations, and their entry into, or exclusion from, important social connections. Built on the results from the India Human Development Survey (IHDS) of over 41,500 households, this report informs a wide range of contemporary debates and policy challenges.